2003
DOI: 10.1590/s1415-47572003000300017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship in Coffea species and parentage determination of interspecific hybrids using ISSR (Inter- Simple Sequence Repeat) markers

Abstract: Inter-simple sequence repeat (ISSR) markers were used to evaluate genetic divergence among eight Coffea species and to identify the parentage of six interspecific hybrids. A total of 14 primers which contained different simple sequence repeats (SSR) were used as single primers or combined in pairs and tested for PCR amplifications. Two hundred and thirty highly reproducible fragments were amplified, which were then used to estimate the genetic similarity and to cluster the Coffea species and hybrids. High leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 37 publications
6
35
0
2
Order By: Relevance
“…These properties have made the markers useful for the genetic analysis of various plants (Reddy et al, 2002). Our results agreed with those of Ruas et al (2003), who reported the use of 14 ISSR primers to evaluate the genetic similarity of 8 species of coffee and to identify the parentage of 6 interspecific hybrids. Similarly, Carvalho et al (2005) have used 30 ISSR primers to confirm the interspecific hybrids of 3 crosses of the Triticeae tribe and found that 13-20 ISSR primers gave polymorphic DNA bands between male and female parents in each cross and could verify their interspecific hybrids.…”
Section: Discussionsupporting
confidence: 91%
“…These properties have made the markers useful for the genetic analysis of various plants (Reddy et al, 2002). Our results agreed with those of Ruas et al (2003), who reported the use of 14 ISSR primers to evaluate the genetic similarity of 8 species of coffee and to identify the parentage of 6 interspecific hybrids. Similarly, Carvalho et al (2005) have used 30 ISSR primers to confirm the interspecific hybrids of 3 crosses of the Triticeae tribe and found that 13-20 ISSR primers gave polymorphic DNA bands between male and female parents in each cross and could verify their interspecific hybrids.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, Ruas et al (2003) revealed the efficiency of markers in the genetic differentiation between Coffea species and the parents identification of interspecific hybrids; and even, for Opuntia, Helsen et al (2009) (Lau et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, molecular markers, such as RFLP, SSR, ISSR, and AFLP, which are usually used to detect DNA polymorphism, were also used for identification of hybrids (Rajora and Rahman, 2003;Ruas et al, 2003;Shasany et al, 2005). Simple sequence repeat (SSR) markers are very advantageous for hybrid identification, but the development of SSR markers is time-consuming and costly, and it requires known corresponding genomic information.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional method for hybrid bamboo identification, which is based on morphological characteristics, is usually affected by environmental factors, and it is difficult to identify hybrids at an early stage. Molecular markers, such as RFLP, SSR, ISSR, and AFLP, used to detect DNA polymorphism, are currently widely used for the identification of artificial and natural hybrids in many plants (Wolfe et al, 1998;Rajora and Rahman, 2003;Ruas et al, 2003;Shasany et al, 2005). We crossbred two bamboo species, Phyllostachys kwangsiensis (female parent) and Ph.…”
Section: Introductionmentioning
confidence: 99%